The Role of Stakeholders In Achieving Surabaya Zero Child Marriage By 2024 to Realize Gender Equality - Alamsyah, Alamsyah; Sukristyanto, Agus; Maduwinarti, Ayun; Nopriyanto, Windi (Formosa Journal of Applied Sciences, 2024)
This study aims to analyze and describe the Role of Stakeholders in Realizing Surabaya Zero Child Marriage in 2024 to Achieve Gender Equality. This research uses a descriptive qualitative research design. A collaborative network involving the city government, private sector, NGOs, communities, and religious organizations such as Muslimat NU in the city of Surabaya has shown significant results in suppressing the rate of child marriage. Through effective coordination, fair resource distribution, transparent communication, and continuous program innovation, this network has made substantial progress towards the zero child marriage goal. However, there are still areas that require further attention, especially in terms of improving access to resources and strengthening coordination. By continuing to strengthen collaboration and applying lessons from experiences, Surabaya can achieve the goal of completely abolishing child marriage.